A preliminary analysis of possibilities of compensating faults of laser and ultrasonic technologies in surgery - Tadeusz Gudra; Sylwia Muc (Archives of Acoustics, 2014)
The active applications of ultrasounds and laser light in surgery are similar. Both technologies complement each other and allow us to obtain desired effects, eliminating the limitations of ultrasounds and lasers used separately. Therefore what happens very often during a medical procedure is the simultaneous use of these two methods from separate standard devices. Having proved the possibility of acoustic wave propagation through optical fibers, the combination of laser light and ultrasounds in one device seems more effective. A comparative analysis of both systems shows that combining the advantages of ultrasonic devices and lasers in one device allows us to compensate for the faults of each of the technologies and improve the effectiveness of surgical operations. The preliminary tests of the operation of the laserultrasonic cutter produced positive and encouraging results. The combined technology has made it possible to use ultrasounds for endoscope operations and to decrease the power of laser and consequently lessen the risk of burning the quartz tip and the optical fiber. A precise selection of the optical fiber seems to be crucial to obtaining an effective laser-ultrasonic surgical device.What is equally important is the appropriate way the light and ultrasonic energies interact.